2012
DOI: 10.1128/jcm.06561-11
|View full text |Cite
|
Sign up to set email alerts
|

Drug and Multidrug Resistance among Mycobacterium leprae Isolates from Brazilian Relapsed Leprosy Patients

Abstract: h Skin biopsy samples from 145 relapse leprosy cases and from five different regions in Brazil were submitted for sequence analysis of part of the genes associated with Mycobacterium leprae drug resistance. Single nucleotide polymorphisms (SNPs) in these genes were observed in M. leprae from 4 out of 92 cases with positive amplification (4.3%) and included a case with a mutation in rpoB only, another sample with SNPs in both folP1 and rpoB, and two cases showing mutations in folP1, rpoB, and gyrA, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 27 publications
4
41
1
2
Order By: Relevance
“…16,17,18,19 . Contudo, faz-se necessário ainda, ressaltar que o predomínio de formas bacilíferas, traduz a permanência de focos de contágio, o que deve colocar os profissionais em alerta para o controle da adesão ao tratamento e de seus comunicantes.…”
Section: Introductionunclassified
“…16,17,18,19 . Contudo, faz-se necessário ainda, ressaltar que o predomínio de formas bacilíferas, traduz a permanência de focos de contágio, o que deve colocar os profissionais em alerta para o controle da adesão ao tratamento e de seus comunicantes.…”
Section: Introductionunclassified
“…Na Bahia, muitos desses casos são diagnosticados e tratados fora de centros de referência, e uma minoria realiza baciloscopia e tem a sua avaliação do comprometimento neural registrado 35 , fatos que tornam emblemática a necessidade de se discutir a qualidade deste diagnóstico, assim como o acesso a serviços especializados de maior complexidade tecnológica regionalizados, sobretudo para municípios de pequeno porte, maioria nesse estado 36 . Ressalta-se ainda a verificação da presença de casos com resistência medicamentosa no país, o que torna a discussão sobre recidivas ainda mais complexa 37 .…”
Section: Discussionunclassified
“…Haldar et al found a 2.6 higher risk of relapse in patients living with active leprosy cases [41], while Rocha et al observed that 31% of the 145 cases with relapse had had relatives who were diagnosed within the 5-year period prior to relapse diagnosis [42].…”
Section: ■ Relapsementioning
confidence: 99%
“…Various researchers agree there is a subset of MB patients, particularly those at the lepromatous pole of the spectrum and those with a high bacterial burden, who are at substantial risk for relapse [42][43][44][45]. Other risk factors include inadequate therapy and immunosuppression [22,[46][47][48].…”
Section: ■ Relapsementioning
confidence: 99%